2018
DOI: 10.1029/2018jb015911
|View full text |Cite
|
Sign up to set email alerts
|

Application of Machine Learning to Classification of Volcanic Deformation in Routinely Generated InSAR Data

Abstract: Recent improvements in the frequency, type, and availability of satellite images mean it is now feasible to routinely study volcanoes in remote and inaccessible regions, including those with no ground‐based monitoring. In particular, Interferometric Synthetic Aperture Radar data can detect surface deformation, which has a strong statistical link to eruption. However, the data set produced by the recently launched Sentinel‐1 satellite is too large to be manually analyzed on a global basis. In this study, we sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
158
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 162 publications
(159 citation statements)
references
References 56 publications
1
158
0
Order By: Relevance
“…For the DCNN models, an advanced type of deep learning models, the features useful for robust classification are dug out from data, instead of being predefined. This idea is repeatedly verified in the computer vision community (Russakovsky et al, ) as well as in the geophysics community (Reichstein et al, ; J. Zhang et al, ; Anantrasirichai et al, ). There are several existing studies for DCNN‐based flooding mapping.…”
Section: Introductionmentioning
confidence: 78%
“…For the DCNN models, an advanced type of deep learning models, the features useful for robust classification are dug out from data, instead of being predefined. This idea is repeatedly verified in the computer vision community (Russakovsky et al, ) as well as in the geophysics community (Reichstein et al, ; J. Zhang et al, ; Anantrasirichai et al, ). There are several existing studies for DCNN‐based flooding mapping.…”
Section: Introductionmentioning
confidence: 78%
“…Deep convolutional neural networks (CNN) -a class of neural networks inspired by deeply complex hierarchical structure of neurons that connect in multiple layers via learnable filters [11] -is one of the feasible methods for automatically analysing global datasets. Our previous 'proof-of-concept' study demonstrated the ability of CNNs to detect rapidly deforming systems that generate multiple fringes in wrapped interferograms [12] but could not reliably distinguish between deformation signals and atmospheric artefacts in a small percentage of cases. Our approach is to use machine learning to interrogate the large dataset of wrapped interferograms and identify a subset of images to apply unwrapping algorithms and atmospheric corrections.…”
Section: Introductionmentioning
confidence: 94%
“…al. [12] used a dataset of >30,000 Sentinel-1 interferograms produced by the LICSAR system which covered ∼900 volcanoes globally, but only contains 42 interferograms that show deformation signals. The imbalance in training data can be mitigated by artificially subsampling or upsampling the training set.…”
Section: Introductionmentioning
confidence: 99%
“…In volcanology, an early application of machine learning (in this case, pattern recognition) investigated preeruptive seismic data during 217 episodes of volcanic unrest around the world . To date, however, machine learning algorithms have seen the widest use not directly in eruption forecasting (see 10.1029/2018JB016974 Brancato et al (2016), however, for an early example), but rather in the related problems of detection and classification of seismic signals (Curilem et al, 2009;Esposito et al, 2006Esposito et al, , 2008Ibs-von Seht, 2008;Masotti et al, 2006;Scarpetta et al, 2005), thermal anomalies (from remote sensing data; Piscini & Lombardo, 2014), and satellite-measured ground deformation (Anantrasirichai et al, 2018). These studies demonstrate the importance of machine learning for "data discovery," which can feed directly into forecasts.…”
Section: Pattern Recognition: Quantitative Approachesmentioning
confidence: 99%